1975
DOI: 10.1152/ajplegacy.1975.228.4.1217
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary effects of paraquat in the first day after injection

Abstract: To learn whether surface force changes precede the appearance of lung edema during experimental intoxication due to paraquat, we studied rats for 1 day following injection of 27 mg/kg iv. By 24 h, surface-active material recovered by lung lavage was decreased 32 percent, and changes in lung microsections and recoil pressure at half-deflation suggested decreased alveolar stability. Despite a 25 percent loss in overall body weight, lung weight increased more than 7 percent and protein concentration in lung lavag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…The results of this study are in line with several other reports [5][6][7]15]. We confirmed the suggestion by FISHER et al [5] that intra-alveolar oedema is present within 24 h after paraquat intoxication and that this model is a model not of primary surfactant synthesis damage, but of surfactant inhibition.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results of this study are in line with several other reports [5][6][7]15]. We confirmed the suggestion by FISHER et al [5] that intra-alveolar oedema is present within 24 h after paraquat intoxication and that this model is a model not of primary surfactant synthesis damage, but of surfactant inhibition.…”
Section: Discussionsupporting
confidence: 94%
“…We confirmed the suggestion by FISHER et al [5] that intra-alveolar oedema is present within 24 h after paraquat intoxication and that this model is a model not of primary surfactant synthesis damage, but of surfactant inhibition. The increased total protein and raised minimal surface tension at 24 h after intoxication clearly show that the properties of surfactant in the alveoli are changing.…”
Section: Discussionsupporting
confidence: 92%
“…Unlike SP-D ϩ/ϩ animals, SP-D Ϫ/Ϫ mice were able to maintain higher BAL phospholipid levels, phospholipidassociated SP-B, and surfactant function early in hyperoxic exposure. Several previous studies have shown that exposure of rodents to either prolonged periods of hyperoxia or to oxidizing agents such as paraquat to induce a relatively severe oxidative insult resulted in significant lung dysfunction that was associated with oxidative changes in endogenous surfactant (29,37,50,68) and depletion of surfactant phospholipid and surfactant proteins (35). Instillation of exogenous surfactant has been shown to attenuate the degree of alveolar injury caused by hyperoxia resulting in improved survival (51).…”
Section: Ablation Of the Sp-d Gene Results In Progressive Alveolar Prmentioning
confidence: 99%
“…Thus, it has been suggested that paraquatstimulated NADPH depletion may be a primary toxic event, in that this effect would be expected to perturb several important cell processess (49,71,(101)(102)(103) (102). These investigators also found that the activity of the pentosephosphate pathway was increased in lungs of rats after intravenous administration of paraquat or diquat (a closely related bipyridylium herbicide capable of redox cycling but not accumulated into lung tissue).…”
Section: Other Potential Superoxide-mediated Reactionsmentioning
confidence: 99%